(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
In Hungary the entire reform of education is going on. New types of institutions, trainings appear. The National Curriculum is under revision. The nationalization of the institutions, the introduction of the supervisory system and the teachers’ career model were important steps. The study deals with the pros and cons of the necessity of the introduction of the career model. Through the description of the situation of public education it can be seen that a step had to be taken to avoid „functional illiteracy”. It is because our falling behind has been increasing compared not only to OECD states, but to our earlier performance as well. It makes a comparison between the teachers’ career model and the performance-linked wage-payment which functions excellently in the competitive sector. The categories of the career model are introduced in a few sentences and the way the teacher can access them.